An Informal Model of Stakeholder's Welfare for Responsible Innovation - Khairil Annuar, Mohd Kamal (Social Science Electronic Publishing, 2016)
In this paper I illustrate a simple informal model to explain how a firm or business organization in its efforts in conducting innovation, may affect the welfare of a stakeholder. In this simple model, time is partitioned into three periods and the business organization’s effort to innovate may yield three different outcomes (either positive or negative or neutral effects) to stakeholder welfare.